2018
DOI: 10.1111/avj.12673
|View full text |Cite
|
Sign up to set email alerts
|

Internal fixation of proximal fractures of the 2nd and 4th metacarpal and metatarsal bones using bioabsorbable screws

Abstract: The use of bioabsorbable screws for fixation of proximal fractures of the splint bone appears to be a safe and feasible technique and may offer several advantages over the use of traditional metallic implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…A paper from the equine medicine and surgery clinic in Lüsche in Germany describes their successful results in 8 horses with fractured splint bones that had internal fixation using bioabsorbable screws …”
Section: Equinementioning
confidence: 99%
See 1 more Smart Citation
“…A paper from the equine medicine and surgery clinic in Lüsche in Germany describes their successful results in 8 horses with fractured splint bones that had internal fixation using bioabsorbable screws …”
Section: Equinementioning
confidence: 99%
“…A paper from the equine medicine and surgery clinic in Lüsche in Germany describes their successful results in 8 horses with fractured splint bones that had internal fixation using bioabsorbable screws. 5 In horses, these fractures are generally treated by removing the distal portion of the bone with or without internal fixation using metallic screws. This may result in postoperative infection, and a second surgery to remove the screws.…”
Section: Equinementioning
confidence: 99%
“…The aim of this retrospective case series by Mahmoud Mageed and colleagues in Germany was to describe the clinical presentation and evaluate the efficacy of bioabsorbable polylactic acid screws in internal fixation of proximal fractures of the second and fourth metacarpal and metatarsal bones in horses .…”
Section: Internal Fixation Of Splint Bone Fracturesmentioning
confidence: 99%
“…Wall et al [11] reported successfully using bioabsorbable screw to bridge the physis of long bones in foals as a means of correcting angular limb deformities. Pyles et al [12] investigated the efficacy of using a bioabsorbable screw to repair an induced fracture in the proximal sesamoid bone, while Mageed et al [13] reported using bioabsorbable screws to treat a splint bone fracture. All the aforementioned studies used implants made of polymers.…”
Section: Introductionmentioning
confidence: 99%